Development of a Pixhawk-Based Quadcopter: A Bottom-Up Approach - Mishra A.; Chitransh V.; Kumar J.; Tiwari N. (My University, 2025)
In this paper, the step-by-step design procedure for the development of a Pixhawk-based quadcopter drone is presented. The purpose of this article is to provide detailed information about building a quadcopter drone in a systematic manner. This article covers the working principle of quadcopter drones along with the operating procedure of the Pixhawk-Cube flight controller. The essential steps involved in drone development such as firmware updating, radio communication, motor testing, and calibration are discussed in detail. To confirm the effectiveness of these development steps, a Pixhawk-based quadcopter drone is developed and its performance is tested by plotting a current to throttle graph. All the steps and procedures suggested by the authors have been suggested from their own experience of drone development. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.